ANTIOXIDANT ACTIVITIES OF ETHANOL LEAF EXTRACTS OF PSIDIUM GUAJAVA L., TERMINALIA CATTAPA L. AND THEIR COMBINED FORMULATION - Timothy, Odaro; Ugwu, G. C. (FUDMA JOURNAL OF SCIENCES, 2022)
Free radicals in the body are the cause of many chronic and debilitating conditions in humans by acting as oxidants in the body. This research was aimed at assessing the antioxidant potential of the leaf extracts of Psidium guajava, Terminalia catappa and a combination of both. The leaves of both plants were independently extracted with ethanol. Equal portions of the extracts of both species were also combined to obtain a formulation of ratio 1:1. The extracts were subjected to in vitro assays including DPPH (2, 2-Diphenyl-1-picrylhydrazyl) and nitric oxide scavenging activities, while in vivo antioxidant assays were evaluated by measuring superoxide dismutase (SOD), malondialdehyde (MDA), catalase (CAT) and glutathione peroxidase (GPx) levels in Wistar rats following oral administration of 200, 400 and 800 mg/kg b.wt. respectively of the 1:1 extract formulation. The three extracts demonstrated dose dependent DPPH scavenging activity, although the 1:1 extract formulation was shown to possess lower free radical scavenging activity compared to the individual plant extracts. At the highest dose, the 1:1 extract formulation was shown to have exhibited a higher nitric oxide scavenging activity than the control, gallic acid. The 200 mg/kg b.wt. of 1:1 extracts formulation possess the highest antioxidant activity in the SOD and MDA assays. The study supports that ethanol leaf extracts of P. guajava and T. catappa possess potent antioxidant properties. However, additional work is required to obtain a more effective formulation from a combination of both extracts.